A rare case of spontaneous combined hydropneumothorax in a case of severe COVID pneumonia - Devadoss, Yelamanchi Hanock; Kale, Mahendra Namdev; Shankar, Uma; Yadav, Narender (Indian Journal of Case Reports, 2021)
The combined spontaneous hydropneumothorax in a healthy young female of COVID-19 is relatively rare in the absence of ventilator-induced barotrauma and associated with typical COVID-related coagulopathy and inflammation. Here, we present the case of a 32-year-old COVID-19-positive female who developed sudden breathlessness and tachycardia. On clinical evaluation and imaging studies, she was found to have hydropneumothorax along with high D-dimer levels. Although the exact cause for this complication is not known, the COVID-19-related coagulopathy and inflammatory response are the likely cause. Monitoring D-dimer levels and early intervention by putting intercostal drain can be life-saving.